Application of biochemical products as a bioremediation technique for domestic sewage treatment - Salim, Mohd. Razman; Md. Hassan, R.; Tan, K. Y. (IWA Publishing, 2007)
Biochemical products have been widely used for treatment of various types of wastewater. The treatment processes with the addition of biochemical products are quite attractive because of their simplicity, minimal use of equipment, they are environmentally friendly and are suitable for the removal of organic pollutants. The purpose of these products is to enhance the activities of beneficial microbes in order to improve treatment performance. This study was carried out to determine the potential of applying biochemical products in assisting and improving the performance of sewage treatment plants. In this study, four biochemical products, namely: Zeolite, Bio-C, Eco-B and Was-D, were applied to the sewage treatment plant. Analyses were carried out on several water quality parameters such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), suspended solids (SS), oil & grease (O&G), phosphorus (P), ammoniacal nitrogen (AN) and sludge thickness (ST). From the results obtained, it can be seen that the overall performance of the treatment plant improved with most of the parameters studied were found to fulfill the DOE Standard B requirements. The performance of Bio-C was found to give better results than other products.